Gamificação na EPT: uma prática pedagógica em tempo de era digital - Silvia, Andréia Gonçalves da (2023)
Based on EPT documents, this research is located in Line 1: Educational Practices in EPT, and in macroproject 1: Methodological proposals and didactic resources in formal and non-formal teaching spaces in EPT and aimed to investigate the gamification within the teaching practice from the Professional and Technological Education - EPT in time of the Digital Era, highlighting the digital inequality presented with greater evidence by the Emergency Remote Teaching (ERE) in the period of the pandemic caused by the SARS-CoV-2 (Covid-19). Such context, experienced in this period with more intensity, instigated us to think about the teaching and learning process and the usual and contemporary ways of teaching. Given this scenario, we explore teaching practice in the face of this changing reality that digital acceleration has brought to the educational community and is still little explored in EPT, as presented by the study. For the development of this research, we had the participation of 9 teachers from the EPT who work with young people aged 14 to 24 who are part of the learning program of the National Service of Commercial Learning - Manaus Unit - SENAC. For this study, we used research of an applied nature, with a qualitative approach. For data collection we used bibliographical and documentary research and forms. The forms were applied to identify: the digital information and communication technologies - TDICs in the educational context of the teachers, the digital and technological resources used by them more frequently, the digital and analogical didactic strategies used by the teachers, the game elements that the teachers use in their pedagogical practice and if they use them, the challenges and difficulties of teaching practice in the digital age and their role in the integral human formation of the student and in their formation for work, having work as an educational principle. From the results obtained with the research, an e-book was elaborated that works as a guide for gamified educational practices that allows the teacher to understand the functioning of gamification beyond digital media, because, according to the results of the research teachers do not use this practice correctly, use it incorrectly or still do not use this methodology in their teaching practice.